A Novel Polyvalent Bacteriophage vB_EcoM_swi3 Infects Pathogenic Escherichia coli and Salmonella enteritidis - Sui, Bingrui; Han, Lili; Ren, Huiying; Liu, Wenhua; Zhang, Can (Frontiers in Microbiology, 2021)
A novel virulent bacteriophage vB_EcoM_swi3 (swi3), isolated from swine feces, could lyse 9% (6/65) of Escherichia coli and 54% (39/72) of Salmonella enteritidis, which were all clinical pathogenic multidrug-resistant strains. The morphological observation showed that phage swi3 belonged to Myoviridae family with an icosahedral head (80 nm in diameter) and a contractile sheathed tail (120 nm in length). At the optimal MOI of 1, the one-step growth analysis of swi3 showed a 25 min latent period with a 25 PFU/infected cell burst size. Phage swi3 could keep stable both at pH 6.0-8.0 and less than 50°C for at least 1 h. Genomic sequencing and bioinformatics analysis based on genomic sequence and the terminase large subunit showed that phage swi3 was a novel member that was most closely related to Salmonella phage and belonged to Rosemountvirus genus. Phage swi3 harbored a 52-kb double-stranded DNA genome with a 46.02% GC content. Seventy-two potential open reading frames were identified and annotated, only 15 of which had been assigned to functional genes. None gene associated with pathogenicity and virulence was identified. The effects of phage swi3 in treating pathologic E. coli infections in vivo were evaluated using a mouse model. The administration of a single intraperitoneal injection of swi3 (106 PFU) at 2 h after challenge with E. coli strain (serotype K88) (108 CFU) could sufficiently protect all mouse without toxic side effect. The finding highlighted the phage swi3 might be used as an effective antibacterial agent to prevent E. coli and S. enteritidis infection.